2008
DOI: 10.1007/s00018-008-8441-3
|View full text |Cite
|
Sign up to set email alerts
|

Progesterone inhibits human endothelial cell proliferation through a p53-dependent pathway

Abstract: Previous studies have shown that progesterone inhibits endothelial cell proliferation through a nuclear receptor-mediated mechanism. Here, we further demonstrate that progesterone at physiologic levels (5 - 500 nM) dose- and time-dependently inhibited DNA synthesis of cultured human umbilical vein endothelial cells (HUVEC). The mRNA and protein levels of p21, p27, and p53 in HUVEC were increased by progesterone. The formation of CDK2-p21 and CDK2-p27 were increased and the CDK2 activity was decreased in the pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
19
0
1

Year Published

2009
2009
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 34 publications
(34 reference statements)
3
19
0
1
Order By: Relevance
“…The p28-induced increase in p21 in MCF-7 cells was also accompanied by a time-dependent increase in p27, another member of the Cip/Kip CDK inhibitor family. Hsu et al (43) recently showed that induction of p53 increased both p21 and p27 promoter activity. In addition, p53 DNA-binding activity of the p21 and p27 promoters is reportedly activated by the p53 inducer, progesterone, suggesting that not only p21 but also p27 is transcriptionally regulated by p53 (43).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The p28-induced increase in p21 in MCF-7 cells was also accompanied by a time-dependent increase in p27, another member of the Cip/Kip CDK inhibitor family. Hsu et al (43) recently showed that induction of p53 increased both p21 and p27 promoter activity. In addition, p53 DNA-binding activity of the p21 and p27 promoters is reportedly activated by the p53 inducer, progesterone, suggesting that not only p21 but also p27 is transcriptionally regulated by p53 (43).…”
Section: Discussionmentioning
confidence: 99%
“…Hsu et al (43) recently showed that induction of p53 increased both p21 and p27 promoter activity. In addition, p53 DNA-binding activity of the p21 and p27 promoters is reportedly activated by the p53 inducer, progesterone, suggesting that not only p21 but also p27 is transcriptionally regulated by p53 (43). Collectively, our data suggest that enhancement of p53 levels subsequently upregulates p21 and p27, inducing a significant decrease in intracellular CDK2 and cyclin A levels in MCF-7 cells and inhibition of the cell cycle at G 2 -M (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…To determine the protein-protein interaction, the immunoprecipitation assay was performed as previously described [10].…”
Section: Immunoprecipitationmentioning
confidence: 99%
“…The Matrigel angiogenesis assay was performed as previously [10,13]. A 500 lL portion of a liquid mixture of Matrigel (350 lL, BD Biosciences, CA), M199 medium (150 lL) and VEGF (50 ng/mL) with or without FA was injected subcutaneously into 7-week-old C57/BL6 male mice (8 mice in each group).…”
Section: Matrigel Angiogenesis Assaymentioning
confidence: 99%
“…Progesterone has also shown several other beneficial effects on the vasculature. It protects against atherosclerosis by inhibiting smooth muscle proliferation in human and rat aortic smooth muscle cells (19,20), which may be mediated via a p53-dependent pathway (15). In ovariectomized rats with pulmonary hypertension, treatment with progesterone decreased the severity of hypertension, decreased vascular remodeling, and decreased mortality (45).…”
Section: Ajp-heart Circ Physiolmentioning
confidence: 99%